The Patient's Family Knowledge Level About Self-Care In Family Members Who Have Stroke - Nuswatul Khaira; Asri Jumadewi; Putro Simeulu; Hilma Yasni; Mutajaridah (Nur Science Institute, 2022)
Stroke is a disease that takes a long time to heal. The recovery of stroke patients is strongly influenced by the knowledge of patients and family members in performing self-care. The purpose of this study was to describe the level of family knowledge about self care in family members who experienced stroke at Yulidin Away Hospital Tapaktuan. The research design used is a quantitative design with a descriptive method. The sampling technique is accidental sampling with the number of respondents as many as 20 people. The results showed that the level of family knowledge about Self-Care based on the Knowledge Level was in the sufficient category, namely 90%, the knowledge level based on the Understanding Level was in the good category, namely 60%, and the knowledge level based on the Applying Level was in the good category, namely 60%. . This study shows the level of family knowledge about Self-Care as a whole is in the good category. Thus, it is hoped that Yulidin Away Hospital can increase information about Self-Care and motivate families in carrying out preventive and rehabilitative efforts in stroke patients.